2021
DOI: 10.5194/bg-18-1-2021
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling <i>Carex brevicuspis</i> leaf litter decomposition and its contribution to surface soil organic carbon pool at different water levels

Abstract: Abstract. Litter decomposition plays a vital role in wetland carbon cycling. However, the contribution of aboveground litter decomposition to the wetland soil organic carbon (SOC) pool has not yet been quantified. Here, we conducted a Carex brevicuspis leaf litter input experiment to clarify the intrinsic factors controlling litter decomposition and quantify its contribution to the SOC pool at different water levels. The Carex genus is ubiquitous in global freshwater wetlands. We sampled this plant leaf litter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This was reflected in the progressive increase in BP, their variable initial growth rates (µ BP ranged from 0.02 to 0.06 h −1 in control tanks according to the experiment) as well as increasing TAA/DOC ratios at the three stations. Finally, an initial increase in BP during incubations is generally described and classically attributed to a bottle effect, which favors large, fast-growing bacteria and often induces mortality of some phytoplankton cells (Calvo-Díaz et al, 2011;Ferguson et al, 1984;Zobell and Anderson, 1936).…”
Section: Inorganic and Organic Materials Exportmentioning
confidence: 99%
“…This was reflected in the progressive increase in BP, their variable initial growth rates (µ BP ranged from 0.02 to 0.06 h −1 in control tanks according to the experiment) as well as increasing TAA/DOC ratios at the three stations. Finally, an initial increase in BP during incubations is generally described and classically attributed to a bottle effect, which favors large, fast-growing bacteria and often induces mortality of some phytoplankton cells (Calvo-Díaz et al, 2011;Ferguson et al, 1984;Zobell and Anderson, 1936).…”
Section: Inorganic and Organic Materials Exportmentioning
confidence: 99%
“…While ergosterol concentration was higher in the T‐A than in the AQ condition in N. antarctica , the opposite was found in P. anserina , where fungal biomass in submerged detritus surpassed the accrual under terrestrial conditions. Some authors found higher fungal biomass in water‐logging conditions compared to leaf litter incubated in wetlands (Zhu et al, 2021) and streams (Abelho & Descals, 2019) others found higher fungal biomass in the river channel than in floodplain ponds (Baldy et al, 2002; Langhans et al, 2008), and other reported no effect (Northington & Webster, 2017). Abelho and Descals (2019) found a decreased reproductive activity of aquatic fungi (hyphomycetes) in litter exposed to an initial terrestrial phase and suggested that this was because terrestrial fungi could not cope with the aquatic condition and therefore did not sporulate.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the structural C content fundamentally determines the duration of the complete decomposition process. 78 For example, the decomposition rate of the submerged macrophyte C. demersum is faster than that of the emergent macrophyte P. australis owing to C. demersum's low C proportion. 79 Conversely, biological components containing N and P are chemically active and easily decomposed, and are released in large quantities during the initial leaching stage.…”
Section: Litter Quality Linked To Amd and The Mechanisms Associated W...mentioning
confidence: 99%
“…The predominantly C-based compounds in plant litter mainly comprise chemically inactive structural C. Structural C is composed mainly of cellulose, hemicellulose, and lignin, which are notably resistant to breakdown and decay compared with other plant components. Consequently, the structural C content fundamentally determines the duration of the complete decomposition process . For example, the decomposition rate of the submerged macrophyte C. demersum is faster than that of the emergent macrophyte P. australis owing to C. demersum ’s low C proportion .…”
Section: Litter Quality Linked To Amd and The Mechanisms Associated W...mentioning
confidence: 99%